Peran Pergaulan antar Teman dalam Menjaga Kesehatan Mental dan Emosional - Rostiawan, Fitra Fajar; Febriansyah, Agung Dwi; Mu'arifah, Alif (Universitas Mathla'ul Anwar Banten, 2025)
The function of peer interactions in promoting the mental and emotional well-being of adolescents is examined in this study. The issue discussed is how friendships can either improve psychological health or, in the case of toxic connections, exacerbate mental health issues like anxiety and despair. This study used a literature review approach to examine academic papers on peer interactions and their psychological effects that were published between 2015 and 2024. Research shows that while toxic friendships increase the likelihood of stress and emotional disorders, positive peer connections greatly enhance psychological resilience and emotional regulation. The study's conclusion highlights the value of communities, families, and educational institutions in creating healthy social relationships that support teenagers' mental health.